The persistent traumatic experience of poverty among the refugees from Mozambique living in the Bushbuckridge area : a challenge to pastoral care - Masango, Maake J.S (University of Pretoria, 2013)
Dissertation (MA (Theology) : Practical Theology)--University of Pretoria, 2008.